Планарии юго-восточной части Украинских Карпат - Чернышева, А.О. (Вестник зоологии, 1993)
4 species of 2 families are found in the studied area: Crenobia alpina and Phagocala vitta (Planariidae) and Dugesia go-nocephala and D lugubris (Dugesiidae). Data on habitat distribution and occurrence.